Optical resin composition and optical resin sheet

By using a composition of a crosslinkable functional group-containing acrylic polymer and a high weight average molecular weight polyisocyanate crosslinking agent, the transparency, adhesion and bending resistance of the optical member in a flexible and foldable display environment are solved. Achieve excellent performance.

CN115141445BActive Publication Date: 2024-12-24ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202210324121.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-31
Filing Date
2022-03-29
Publication Date
2024-12-24
Estimated Expiration
2042-03-29

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the transparency, adhesion, retention and bending resistance of optical components, especially in flexible and foldable display environments, where the performance requirements of the adhesive are higher.

Method used

The composition of acrylic polymer containing crosslinking functional groups and an aliphatic or cycloaliphatic polyisocyanate crosslinking agent with high weight average molecular weight is used to form excellent adhesion and retain through specific crosslinking agent components and proportions. An optical resin composition with force and bending resistance.

Benefits of technology

It realizes good transparency, strong adhesion, retention and bending resistance of optical resin sheets, and is suitable for optical components of flexible and foldable displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003571174950000341
    Figure BDA0003571174950000341
  • Figure BDA0003571174950000342
    Figure BDA0003571174950000342
  • Figure BDA0003571174950000381
    Figure BDA0003571174950000381
Patent Text Reader

Abstract

Optical resin composition and optical resin sheet. [Subject] To provide an optical resin composition that maintains good transparency when forming an optical resin sheet and has excellent adhesion, holding power and bending resistance. [Solution] An optical resin composition, which contains an acrylic polymer (A) and a crosslinking agent component (B), wherein the acrylic polymer (A) is a monomer containing a crosslinking functional group and a (meth)acrylate monomer having a carbon number of 1 to 18 at the end of the ester group, the glass transition temperature Tg of the acrylic polymer (A) is below ‑10.0°C, and the crosslinking agent component (B) contains an aliphatic or alicyclic polyisocyanate having a weight average molecular weight of 2100 to 200000.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical resin composition and an optical resin sheet. Background Art

[0002] In recent years, due to the high-definition image quality, touch panelization, flexibility of displays, and diversification of places of use, optical components such as adhesives, bonding agents, and films for displays are not only required to be transparent and have a certain bonding strength, but also require various properties such as high weather resistance, high transparency, strong bonding force, high moisture and heat resistance, bending resistance, reprocessability, and control of electrical properties. In particular, due to the flexibility and foldability of displays, the performance required for adhesives and bonding agents that bond optical components to each other is further improved. Specifically, it is required to maintain transparency, and require strong bonding force, high cohesion (high retention), bending resistance, and other properties.

[0003] For example, Patent Document 1 discloses a pressure-sensitive adhesive composition comprising an acrylic polymer having a specific structure and an organic polyisocyanate crosslinking agent or an epoxy crosslinking agent. The invention discloses that the pressure-sensitive adhesive composition can provide a film having excellent stress dispersion properties.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-132872 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] However, there is a demand for a technology that maintains transparency and has better adhesive force, holding power, and bending resistance than the technology described in Patent Document 1. In particular, with the recent launch of foldable displays, bending resistance has become an important performance.

[0009] The present invention has been made in view of the above circumstances, and provides an optical resin composition which maintains good transparency when formed into an optical resin sheet and has excellent adhesive strength, holding power and bending resistance, and an optical resin sheet formed using the optical resin composition.

[0010] Solutions for solving problems

[0011] That is, the present invention includes the following aspects.

[0012] (1) An optical resin composition comprising an acrylic polymer (A) and a crosslinking agent component (B),

[0013] The acrylic polymer (A) is obtained by copolymerizing a monomer containing a crosslinkable functional group and a (meth)acrylic acid ester monomer having 1 to 18 carbon atoms at the terminal ester group.

[0014] The glass transition temperature Tg of the acrylic polymer (A) is -10.0°C or lower,

[0015] The crosslinking agent component (B) contains an aliphatic or alicyclic polyisocyanate having a weight average molecular weight of 2,100 to 200,000.

[0016] (2) The optical resin composition according to (1), wherein the average number of isocyanate groups of the crosslinking agent component (B) is 2.0 or more and 6.5 or less.

[0017] (3) The optical resin composition according to (1) or (2), wherein the content of the crosslinking agent component (B) is 0.01 parts by mass or more and 5.0 parts by mass or less per 100 parts by mass of the acrylic polymer (A).

[0018] (4) The optical resin composition according to any one of (1) to (3), wherein the weight average molecular weight of the acrylic polymer (A) is 5.0×10 5 Above and 5.0×10 6 the following.

[0019] (5) The optical resin composition according to any one of (1) to (4), wherein the crosslinkable functional group is one or more selected from the group consisting of a hydroxyl group, an epoxy group, a carboxyl group, and a vinyl group.

[0020] (6) The optical resin composition according to any one of (1) to (5), wherein the content of the structural unit derived from the (meth)acrylate monomer is 0.01% by mass or more and 99.99% by mass or less based on the total mass of the acrylic polymer (A).

[0021] (7) The optical resin composition according to any one of (1) to (6), wherein the aliphatic or alicyclic polyisocyanate is a polyisocyanate derived from at least one diisocyanate (b1) selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates, a bifunctional polyol (b2) having a number average molecular weight of 1,500 or more, and a trifunctional or higher polyol (b3) having a number average molecular weight of 500 or more.

[0022] The ratio NCO / OH of the molar amount of the isocyanate group of the diisocyanate (b1) to the total molar amount of the hydroxyl groups of the polyol (b2) and the polyol (b3) is 3 or more and 30 or less.

[0023] (8) The optical resin composition according to (7), wherein the mass ratio of the polyol (b3) to the polyol (b2) (b3) / (b2) is 0.1 / 99.9 or more and 99.9 / 0.1 or less, and

[0024] With respect to 100 parts by mass of the diisocyanate (b1),

[0025] The content of the polyol (b2) is 0.1 parts by mass or more and 250 parts by mass or less,

[0026] The content of the polyol (b3) is 0.1 parts by mass or more and 190 parts by mass or less.

[0027] (9) The optical resin composition according to (7) or (8), wherein the polyol (b2) and the polyol (b3) are at least one polyol selected from the group consisting of polyester polyols, polyether polyols, epoxy polyols, polyolefin polyols and polycarbonate polyols.

[0028] (10) The optical resin composition according to any one of (1) to (9), wherein the isocyanate group content of the crosslinking agent component (B) is 1% by mass or more and 10% by mass or less.

[0029] (11) The optical resin composition according to any one of (1) to (10), further comprising 0.01 parts by mass or more and 0.5 parts by mass or less of a silane coupling agent (C) based on 100 parts by mass of the acrylic polymer (A).

[0030] (12) The optical resin composition according to any one of (1) to (11), wherein the crosslinking agent component (B) contains one or more selected from the group consisting of isocyanate compounds other than the aliphatic or alicyclic polyisocyanates, carbodiimide compounds, oxazoline compounds, polyfunctional acrylate monomers, peroxides, titanium coupling agents, zirconium compounds, metal aluminum chelates, hydrazide compounds, epoxy crosslinking agents, thermal acid generators and photoacid generators.

[0031] (13) The optical resin composition according to any one of (1) to (12), wherein the crosslinking agent component (B) is applied on glass and a cured film having a film thickness of 40 μm formed by storing the film under a 23° C. and 65% humidity environment for 168 hours has a pendulum hardness of ( hardness) is less than 60 times.

[0032] (14) An optical resin sheet obtained by curing the optical resin composition according to any one of (1) to (13) by heat or light.

[0033] (15) The optical resin sheet according to (14), wherein the optical resin sheet has a thickness of 1 μm or more and 1000 μm or less.

[0034] (16) An optical resin sheet according to (14) or (15), wherein the following optical resin sheet is bonded to a SUS304BA plate as an adherend, and after being reciprocally pressed once using a 2kg roller and aging at 23°C for 30 minutes, the 180-degree peel adhesion measured at 23°C and a speed of 300 mm / min is 2.0 N / 20 mm or more and 65 N / 20 mm or less, wherein the optical resin sheet is: an optical resin sheet having a thickness of 70 μm, a width of 20 mm and a length of 100 mm on one side of the polyethylene terephthalate film, obtained by coating the aforementioned optical resin composition on a polyethylene terephthalate film having a thickness of 25 μm, drying at 125°C for 3 minutes to cure, and then storing at 23°C and 50% RH for 7 days.

[0035] (17) An optical resin sheet according to any one of (14) to (16), wherein the optical resin sheet is adhered to a SUS304BA plate as an adherend in an overlapping manner with a width of 25 mm and a length of 25 mm, and is reciprocally pressed once using a 2 kg roller and aged at 23°C for 1 hour. After further aging at 40°C for 30 minutes, a 500 g weight is hung from the lower end of the optical resin sheet at 40°C for 1 hour, and then the displacement of the optical resin sheet when it is restored to 23°C is less than 2 mm / hour, wherein the optical resin sheet is an optical resin sheet having a thickness of 70 μm, a width of 25 mm and a length of 130 mm, obtained by coating the optical resin composition on a polyethylene terephthalate film having a thickness of 25 μm, drying at 125°C for 3 minutes to cure, and then storing at 23°C and 50% RH for 7 days.

[0036] (18) An optical resin sheet according to any one of (14) to (17), wherein the following optical resin sheet is adhered to glass with a haze value of 0.1% and the haze value measured by a haze meter is less than 2.0%, and the optical resin sheet is: the aforementioned optical resin composition is coated on a polyethylene terephthalate film with a thickness of 38 μm, dried at 125°C for 3 minutes to cure, and then stored at 23°C, 50% RH for 7 days to obtain an optical resin sheet with a thickness of 70 μm obtained by peeling off the aforementioned polyethylene terephthalate film after peeling.

[0037] (19) An optical resin sheet according to any one of (14) to (18), wherein the optical resin sheet is stored at 23°C and 50% RH for 7 days, then wrapped in a mesh sheet, immersed in ethyl acetate at 23°C for 1 week, taken out and dried at 120°C for 2 hours, and the gel fraction calculated thereby is 40.0% by mass or more and 99.9% by mass or less, and the optical resin sheet is an optical resin sheet having a thickness of 70 μm obtained by coating the optical resin composition on a release-treated polyethylene terephthalate film having a thickness of 38 μm, drying at 125°C for 3 minutes to cure, and then storing the sheet at 23°C and 50% RH for 7 days and peeling the sheet off from the release-treated polyethylene terephthalate film.

[0038] (20) An optical resin sheet according to any one of (14) to (19), wherein the optical resin sheet is stacked in a manner having a thickness of 210 μm, cut into pieces having a width of 10 mm and a length of 40 mm, and then mounted on a tensile testing machine with a distance between chucks of 10 mm, and the Young's modulus in a tensile test performed at a speed of 300 mm / min at 23° C. is 0.40 N / mm 2 The optical resin sheet is: the optical resin composition is coated on a 38 μm thick release-treated polyethylene terephthalate film, dried at 125° C. for 3 minutes to cure, and then stored at 23° C., 50% RH for 7 days to obtain a 70 μm thick optical resin sheet peeled off from the release-treated polyethylene terephthalate film.

[0039] Effects of the Invention

[0040] According to the optical resin composition of the above embodiment, it is possible to provide an optical resin composition that maintains good transparency when forming an optical resin sheet and has excellent adhesive force, holding power and bending resistance. The optical resin sheet of the above embodiment is formed by curing the optical resin composition, has good transparency, and has excellent adhesive force, holding power and bending resistance. DETAILED DESCRIPTION

[0041] In addition, in this specification, "polyol" refers to a compound having two or more hydroxyl groups (-OH) in one molecule.

[0042] In addition, in this specification, "polyisocyanate" means a reaction product in which a plurality of monomer compounds having two or more isocyanate groups (-NCO) are bonded to each other.

[0043] In addition, in this specification, unless otherwise specified, "(meth)acrylic acid" includes methacrylic acid and acrylic acid, and "(meth)acrylate" includes methacrylate and acrylate.

[0044] 《Optical resin composition》

[0045] The optical resin composition of the present embodiment contains an acrylic polymer (A) and a cross-linking agent component (B).

[0046] The acrylic polymer (A) is a polymer obtained by copolymerizing a crosslinkable functional group-containing monomer and a (meth)acrylic acid ester monomer having 1 to 18 carbon atoms at the terminal ester group.

[0047] The glass transition temperature Tg of the acrylic polymer (A) is -75.0°C to -10.0°C, preferably -74.0°C to -20.0°C, more preferably -73.0°C to -30.0°C, further preferably -72.0°C to -40.0°C, particularly preferably -71.0°C to -50.0°C, and most preferably -71.0°C to -50.0°C. When the glass transition temperature Tg of the acrylic polymer (A) is within the above range, the adhesive force and bending resistance when the optical resin sheet is formed tend to be excellent.

[0048] The glass transition temperature of the acrylic polymer (A) can be, for example, a value obtained by blowing off the organic solvent and water in a solution in which the acrylic polymer (A) is dissolved or dispersed under reduced pressure and then vacuum drying using a differential scanning calorimeter (DSC) measuring apparatus at a heating rate of 5°C / min.

[0049] The crosslinking agent component (B) contains an aliphatic or alicyclic polyisocyanate having a weight average molecular weight of 2,100 to 200,000.

[0050] The optical resin composition of the present embodiment can obtain an optical resin sheet with good transparency and excellent bonding force, holding power and bending resistance by having the above-mentioned technical characteristics. It should be noted that the bending resistance referred to herein is as shown in the embodiments described later, and for the simplification of evaluation, it is evaluated with elastic modulus, maximum stress and elongation, and can be shown by making the elastic modulus (Young's modulus) of the layer formed by curing the optical resin composition low, large elongation and large maximum stress. That is, it is easy to follow the deformation caused by bending, easy to relax stress and not easy to destroy (maximum stress is large), and it is considered that the bending resistance is excellent. The preferred range of Young's modulus is described later.

[0051] <Acrylic polymer (A)>

[0052] The acrylic polymer (A) is a polymer obtained by copolymerizing a crosslinkable functional group-containing monomer (a1) and a (meth)acrylic acid ester monomer (a2) having 1 to 18 carbon atoms at the terminal ester group.

[0053] The monomer (a1) containing a crosslinkable functional group has a polymerizable functional group and a crosslinkable functional group that can form a crosslinked structure with the crosslinking agent component (B). As the polymerizable functional group, for example, vinyl can be listed. In addition, as the crosslinkable functional group, for example, hydroxyl, sulfhydryl, amino, amide, epoxy, carboxyl, vinyl, etc. can be listed, among which hydroxyl, epoxy, or carboxyl, more preferably hydroxyl, is preferred. The crosslinkable functional group can also be imparted by polymerizing acrylate and then modifying it.

[0054] The acrylic polymer (A) may contain only one structural unit derived from a monomer (a1) containing a crosslinkable functional group and one structural unit derived from a (meth)acrylate monomer (a2), or may contain a structural unit derived from a monomer (a1) containing a crosslinkable functional group and a structural unit derived from a (meth)acrylate monomer (a2) in combination of two or more. That is, the acrylic polymer (A) may be a copolymerization of one monomer (a1) containing a crosslinkable functional group and one (meth)acrylate monomer (a2), or may be a copolymerization of two or more monomers (a1) containing a crosslinkable functional group and one (meth)acrylate monomer (a2). It should be noted that the (meth)acrylate monomer (a2) may or may not have a crosslinkable functional group, but preferably does not have a crosslinkable functional group.

[0055] In addition to the structural units derived from the monomer (a1) containing a crosslinkable functional group and the structural units derived from the (meth)acrylate monomer (a2), the acrylic polymer (A) may also contain structural units derived from other polymerizable monomers (a3) ​​(hereinafter sometimes simply referred to as "other polymerizable monomers (a3)"). That is, the acrylic polymer (A) may be copolymerized with one or more monomers (a1) containing a crosslinkable functional group, one or more (meth)acrylate monomers (a2), and one or more other polymerizable monomers (a3). It should be noted that the other polymerizable monomers (a3) ​​may or may not have a crosslinkable functional group.

[0056] As the crosslinkable functional group-containing monomer (a1), a polymerizable (meth)acrylic monomer having a crosslinkable functional group is preferred.

[0057] Examples of the polymerizable (meth)acrylic monomer having a crosslinkable functional group include the polymerizable (meth)acrylic monomers having a crosslinkable functional group shown in (i) to (viii) below. These may be used alone or in combination of two or more.

[0058] (i) Acrylic acid esters having a hydroxyl group such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxybutyl acrylate, 4-hydroxybutyl acrylate, 6-hydroxyhexyl acrylate, and 8-hydroxyoctyl acrylate.

[0059] (ii) Methacrylic acid esters having a hydroxyl group such as 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 4-hydroxybutyl methacrylate, 6-hydroxyhexyl methacrylate, and 8-hydroxyoctyl methacrylate.

[0060] (iii) (meth)acrylates having a polyhydric hydroxyl group, such as monoacrylate or monomethacrylate of glycerol and monoacrylate or monomethacrylate of trimethylolpropane.

[0061] (iv) Unsaturated carboxylic acids such as acrylic acid and methacrylic acid.

[0062] (v) Unsaturated amides such as (meth)acrylamide.

[0063] (vi) (meth)acrylates having an amino group, such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate.

[0064] (vii) (Meth)acrylates having an epoxy group, such as glycidyl methacrylate.

[0065] (viii) (meth)acrylates having a carboxyl group, such as 2-carboxyethyl acrylate and 2-carboxyethyl methacrylate.

[0066] When the polymerizable (meth)acrylic monomer having a crosslinkable functional group is a (meth)acrylic ester monomer having a crosslinkable functional group, the number of carbon atoms in the ester portion is preferably 1 to 18, more preferably 1 to 12, further preferably 1 to 10, particularly preferably 1 to 8, and most preferably 2 to 8.

[0067] The number of carbon atoms at the terminal ester group in the (meth)acrylate monomer (a2) is 1 or more and 18 or less.

[0068] Examples of the (meth)acrylate monomer (a2) include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, and isononyl (meth)acrylate. , decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate (lauryl (meth)acrylate), tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, benzyl (meth)acrylate, cyclohexyl (meth)acrylate and the like (meth)acrylates, etc. These may be used alone or in combination of two or more.

[0069] Examples of the other polymerizable monomer (a3) ​​include the other polymerizable monomers shown in (i) to (iv) below. These can be used alone or in combination of two or more.

[0070] (i) Unsaturated carboxylic acids such as maleic acid and itaconic acid.

[0071] (ii) Monomers having an epoxy group, such as 1,2-epoxy-4-vinylcyclohexane, allyl glycidyl ether, and 4-hydroxybutyl acrylate glycidyl ether.

[0072] (iii) Unsaturated amides such as N-methylol acrylamide, diacetone acrylamide, and dimethylaminopropyl acrylamide.

[0073] (iv) Vinyl acetate, (meth)acrylonitrile, styrene, vinyltoluene, N-vinylpyrrolidone, N-vinylcaprolactam, acryloylmorpholine.

[0074] Furthermore, as other monomers copolymerizable with the crosslinkable functional group-containing monomer (a1) and the (meth)acrylate monomer (a2), polymerizable ultraviolet-stable monomers disclosed in JP-A-1-261409 (reference 1) and JP-A-3-006273 (reference 2) can be used.

[0075] Specific examples of the polymerizable UV-stable monomer include 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-crotonyl-4-crotonyloxy-2,2,6,6-tetramethylpiperidine, and 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone.

[0076] For example, the acrylic polymer (A) can be obtained by subjecting the above-mentioned monomer components to solution polymerization in the presence of a known radical polymerization initiator such as a peroxide or an azo compound, and diluting with an organic solvent or the like as necessary.

[0077] When obtaining an acrylic polymer (A) of a water-based matrix, it can be produced by a known method such as a method of subjecting an olefinic unsaturated compound to solution polymerization and conversion to an aqueous layer, or emulsion polymerization. In this case, water solubility or water dispersibility can be imparted by neutralizing the acidic part of a carboxylic acid-containing monomer such as acrylic acid or methacrylic acid, or a sulfonic acid-containing monomer with amine or ammonia.

[0078] The content of the structural unit derived from the monomer (a1) containing a crosslinkable functional group is preferably 0.01% by mass or more and 25% by mass or less, more preferably 0.02% by mass or more and 23% by mass or less, further preferably 0.03% by mass or more and 21% by mass or less, and particularly preferably 0.04% by mass or more and 20% by mass or less, relative to the total mass of the acrylic polymer (A). When the content of the structural unit derived from the monomer (a1) containing a crosslinkable functional group is within the above numerical range, there is a tendency that the adhesive force and the cohesive force (holding force) when forming the optical resin sheet are more excellent.

[0079] The content of the structural unit derived from the (meth)acrylate monomer (a2) is preferably 0.01% by mass or more and 99.99% by mass or less, more preferably 10% by mass or more and 99.99% by mass or less, further preferably 50% by mass or more and 99.99% by mass or less, and particularly preferably 80% by mass or more and 99.99% by mass or less, relative to the total mass of the acrylic polymer (A). When the content of the structural unit derived from the (meth)acrylate monomer (a2) is within the above numerical range, there is a tendency that the adhesive force and the cohesive force (holding force) when forming the optical resin sheet are more excellent.

[0080] The content of the structural unit derived from the monomer (a1) containing a crosslinkable functional group and the content of the structural unit derived from the (meth)acrylate monomer (a1) can be calculated, for example, from the respective blending amounts of the monomer (a1) containing a crosslinkable functional group and the (meth)acrylate monomer (a2) used in the production of the acrylic polymer (A). 1H-NMR spectroscopy, 12 The composition ratio was calculated by combining C-NMR spectrum, IR spectrum and mass spectrometry.

[0081] The weight average molecular weight Mw(A) of the acrylic polymer (A) is preferably 5.0×10 5 Above and 5.0×10 6 Less than, more preferably 6.0×10 5 Above and 2.5×10 6 Below, more preferably 6.5×10 5 Above and 2.0×10 6 Below, particularly preferably 7.0×10 5 Above and 1.9×10 6 When the weight average molecular weight Mw(A) of the acrylic polymer (A) is within the above range, there is a tendency that the adhesive force, cohesive force (holding force) and moisture and heat resistance durability when forming an optical resin sheet are more excellent. The weight average molecular weight Mw(A) of the acrylic polymer (A) can be measured, for example, using the method described in the examples described below.

[0082] <Crosslinking agent component (B)>

[0083] The crosslinking agent component (B) contains an aliphatic or alicyclic polyisocyanate having a weight average molecular weight of 2,100 or more and 200,000 or less.

[0084] The weight average molecular weight Mw(b) of the aliphatic or alicyclic polyisocyanate is 2100 or more and 200000 or less, preferably 2500 or more and 150000 or less, more preferably 2800 or more and 100000 or less, further preferably 3000 or more and 80000 or less, and particularly preferably 3200 or more and 70000 or less. When the weight average molecular weight Mw(b) of the aliphatic or alicyclic polyisocyanate is within the above numerical range, the elastic modulus (Young's modulus) of the obtained optical resin sheet can be further reduced, the elongation can be further increased, and the breaking strength can be further increased.

[0085] Mw(b) of the aliphatic or alicyclic polyisocyanate is a weight average molecular weight based on polystyrene measured by GPC.

[0086] The average number of isocyanate groups of the aliphatic or alicyclic polyisocyanate is preferably 2.0 to 6.5, more preferably 2.3 to 6.3, further preferably 2.4 to 6.1, and particularly preferably 2.5 to 6.0. When the average number of isocyanate groups of the aliphatic or alicyclic polyisocyanate is within the above numerical range, the acrylic polymer (A) and the crosslinking agent component (B) form a crosslinking network more effectively, and the elongation and breaking strength of the obtained optical resin sheet can be further increased.

[0087] The average number of isocyanate groups (fn) of an aliphatic or alicyclic polyisocyanate can be calculated using the following formula. In the following formula, "Mn" represents the number average molecular weight of the aliphatic or alicyclic polyisocyanate, and "NCO%" represents the isocyanate group content of the aliphatic or alicyclic polyisocyanate. The number average molecular weight Mn of an aliphatic or alicyclic polyisocyanate is a weight average molecular weight based on polystyrene obtained by GPC measurement. The method for determining NCO% is described below.

[0088] [fn] = [Mn] × [NCO%] / 4200

[0089] The aliphatic or alicyclic polyisocyanate (b) is preferably a polyisocyanate derived from at least one diisocyanate (b1) selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates, a bifunctional polyol (b2) having a number average molecular weight of 1500 or more, and a trifunctional or higher polyol (b3) having a number average molecular weight of 500 or more.

[0090] The ratio NCO / OH of the molar amount of the isocyanate group of the diisocyanate (b1) to the total molar amount of the hydroxyl groups of the polyol (b2) and the polyol (b3) is preferably 3 or more and 30 or less, more preferably 4 or more and 25 or less, further preferably 5 or more and 22 or less, and particularly preferably 6 or more and 20 or less. When the NCO / OH ratio is within the above numerical range, the crosslinking agent component (B) can be synthesized without gelation, and the elastic modulus, elongation, and breaking strength of the obtained optical resin sheet can be further reduced.

[0091] The aliphatic or alicyclic polyisocyanate (b) may be a polyisocyanate having in one molecule all of the structural units derived from diisocyanate, polyol (b2) and polyol (b3), or a mixture of polyisocyanates having in one molecule at least one structural unit derived from the group consisting of diisocyanate, polyol (b2) and polyol (b3).

[0092] The aliphatic or alicyclic polyisocyanate (b) may have at least one structure selected from the group consisting of an allophanate structure, a uretdione structure, an iminooxadiazinedione structure, an isocyanurate structure, a urea structure, a carbamate structure, and a biuret structure. Among them, it is preferred to have at least one structure selected from the group consisting of a carbamate structure, an allophanate structure, a biuret structure, a urea structure, and an isocyanurate group, and more preferably contain a carbamate structure.

[0093] [Diisocyanate (b1)]

[0094] The diisocyanate (b1) is at least one selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates.

[0095] The aliphatic diisocyanate is not limited to the following, and examples thereof include 1,4-diisocyanatobutane, 1,5-diisocyanatopentane, ethyl (2,6-diisocyanato)hexanoate, 1,6-hexamethylene diisocyanate (hereinafter sometimes referred to as "HDI"), 1,9-diisocyanatononane, 1,12-diisocyanatododecane, 2,2,4- or 2,4,4-trimethyl-1,6-hexamethylene diisocyanate, etc. These aliphatic diisocyanates may be used alone or in combination of two or more.

[0096] Examples of the alicyclic diisocyanate include, but are not limited to, 1,3- or 1,4-bis(isocyanatomethyl)cyclohexane (hereinafter sometimes referred to as "hydrogenated XDI"), 1,3- or 1,4-diisocyanatocyclohexane, 3,5,5-trimethyl1-isocyanato-3-(isocyanatomethyl)cyclohexane (hereinafter sometimes referred to as "IPDI"), 4-4'-diisocyanato-dicyclohexylmethane (hereinafter sometimes referred to as "hydrogenated MDI"), 2,5- or 2,6-diisocyanatomethylnorbornane, etc. These alicyclic diisocyanates may be used alone or in combination of two or more.

[0097] These aliphatic diisocyanates and alicyclic diisocyanates may be used alone or in combination of two or more.

[0098] From the viewpoint of flexibility, the mass ratio of the alicyclic polyisocyanate to the aliphatic diisocyanate is preferably 0 / 100 or more and 30 / 70 or less, and more preferably 0 / 100 or more and 20 / 80 or less.

[0099] Among them, as the diisocyanate, HDI, IPDI, hydrogenated XDI, or hydrogenated MDI is preferred, HDI or IPDI is more preferred, and HDI is further preferred.

[0100] In order to produce the polyisocyanate, in addition to the above-mentioned diisocyanate, the following isocyanate monomers may be used.

[0101] (1) Aromatic diisocyanates such as diphenylmethane-4,4'-diisocyanate (MDI), 1,5-naphthalene diisocyanate, toluene diisocyanate (TDI), xylylene diisocyanate, and m-tetramethylxylylene diisocyanate (TMXDI).

[0102] (2) Triisocyanates such as 4-isocyanatemethyl-1,8-octamethylene diisocyanate (hereinafter sometimes referred to as "NTI"), 1,3,6-hexamethylene triisocyanate (hereinafter sometimes referred to as "HTI"), bis(2-isocyanatoethyl) 2-isocyanatoglutarate (hereinafter sometimes referred to as "GTI"), and lysine triisocyanate (hereinafter sometimes referred to as "LTI").

[0103] [Polyol (b2) and polyol (b3)]

[0104] The polyol (b2) is a bifunctional polyol (diol) having a number average molecular weight of 1,500 or more.

[0105] The polyol (b3) has a number average molecular weight of 500 or more and is a trifunctional or higher-functional polyol.

[0106] The number average molecular weight of the polyol (b2) is 1500 or more, preferably 1800 or more. When the number average molecular weight of the polyol (b2) is at least the above lower limit, the hardness of a cured film obtained by curing only the polyisocyanate is low and the flexibility is good.

[0107] On the other hand, the upper limit of the number average molecular weight of the polyol (b2) is not particularly limited, and may be, for example, 12,000, preferably 11,000, more preferably 10,000, further preferably 8,000, further preferably 6,000, particularly preferably 5,000, and most preferably 4,200.

[0108] The number average molecular weight Mn of the polyol (b2) is, for example, a polystyrene-based number average molecular weight measured by GPC. When two or more polyols (b2) are mixed and used, the number average molecular weight of the mixture is calculated.

[0109] The number average molecular weight of the polyol (b3) is 500 or more, preferably 800 or more. When the number average molecular weight of the polyol (b3) is at least the above lower limit, the hardness of a cured film obtained by curing only the polyisocyanate is low and the flexibility is good.

[0110] On the other hand, the upper limit of the number average molecular weight of the polyol (b3) is not particularly limited, and may be, for example, 3,000, and preferably 2,200.

[0111] The number average molecular weight Mn of the polyol (b3) is, for example, a polystyrene-based number average molecular weight measured by GPC. When two or more polyols (b3) are mixed and used, the number average molecular weight of the mixture is calculated.

[0112] The polyol (b2) is preferably at least one bifunctional polyol (diol) selected from the group consisting of polyester polyol, polyether polyol, epoxy polyol, polyolefin polyol and polycarbonate polyol, and more preferably a bifunctional polyester polyol.

[0113] Examples of the bifunctional polyester polyol include any of the following (1) and (2).

[0114] (1) A polyester polyol obtained by a condensation reaction of a dibasic acid alone or a mixture of two or more thereof and a diol alone or a mixture of two or more thereof.

[0115] (2) Polycaprolactone polyol obtained by ring-opening polymerization of ε-caprolactone using a diol.

[0116] Examples of the dibasic acid include carboxylic acids such as succinic acid, adipic acid, dimer acid, maleic anhydride, phthalic anhydride, isophthalic acid, terephthalic acid, and 1,4-cyclohexanedicarboxylic acid.

[0117] Examples of the diol include ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, neopentyl glycol, 1,6-hexanediol, trimethylpentanediol, and cyclohexanediol.

[0118] Among them, as the bifunctional polyester polyol, bifunctional polycaprolactone polyol is preferred.

[0119] Examples of commercially available bifunctional polycaprolactone polyols include "PLACCEL 210" (number average molecular weight 1000), "PLACCEL 220" (number average molecular weight 2000), "PLACCEL 230" (number average molecular weight 3000), and "PLACCEL 240" (number average molecular weight 4000) manufactured by Daicel Corporation.

[0120] The polyol (b3) may be a trifunctional or higher polyol, preferably a trifunctional or higher and decafunctional or lower polyol, more preferably a trifunctional or higher and heptafunctional or lower polyol, further preferably a trifunctional or higher and pentafunctional or lower polyol, particularly preferably a trifunctional or higher and tetrafunctional or lower polyol, and most preferably a trifunctional polyol (triol).

[0121] The trifunctional polyol (triol) is preferably at least one trifunctional polyol (triol) selected from the group consisting of polyester polyol, polyether polyol, epoxy polyol, polyolefin polyol and polycarbonate polyol, and more preferably a trifunctional polyester polyol.

[0122] Examples of the trifunctional polyester polyol include any of the following (1) and (2).

[0123] (1) A polyester polyol obtained by a condensation reaction of a dibasic acid alone or a mixture of two or more thereof and a trihydric alcohol alone or a mixture of two or more thereof.

[0124] (2) Polycaprolactone polyol obtained by ring-opening polymerization of ε-caprolactone using a triol.

[0125] Examples of the dibasic acid include carboxylic acids such as succinic acid, adipic acid, dimer acid, maleic anhydride, phthalic anhydride, isophthalic acid, terephthalic acid, and 1,4-cyclohexanedicarboxylic acid.

[0126] Examples of the triol include trimethylolpropane, glycerin, pentaerythritol, 2-methylolpropanediol, and ethoxylated trimethylolpropane.

[0127] Among them, as the trifunctional polyester polyol, a trifunctional polycaprolactone polyol is preferred.

[0128] Examples of commercially available trifunctional polycaprolactone polyols include "PLACCEL 305" (number average molecular weight 550), "PLACCEL 308" (number average molecular weight 850), "PLACCEL 309" (number average molecular weight 900), "PLACCEL 312" (number average molecular weight 1250), and "PLACCEL 320" (number average molecular weight 2000) manufactured by Daicel Corporation.

[0129] In the aliphatic or alicyclic polyisocyanate (b), the mass ratio of the polyol (b2) to the polyol (b3) (mass ratio of (b2) / (b3)) is preferably 0.1 / 99.9 or more and 99.9 / 0.1 or less, more preferably 1 / 99 or more and 99 / 1 or less, further preferably 3 / 97 or more and 90 / 10 or less, particularly preferably 3 / 97 or more and 85 / 15 or less, and most preferably 5 / 95 or more and 80 / 20 or less.

[0130] When the mass ratio of (b2) / (b3) is above the above lower limit, the hardness of the cured film formed by curing the polyisocyanate alone is low and the flexibility is better. In addition, an optical resin sheet with better adhesion and flexibility is obtained. On the other hand, when the mass ratio of (b2) / (b3) is below the above upper limit, an optical resin sheet with better adhesion, flexibility and cohesion is better.

[0131] The mass ratio of (b2) / (b3) can be calculated from the blending amounts of the respective polyols during production of the polyisocyanate, for example.

[0132] In the aliphatic or alicyclic polyisocyanate (b), the content (charge amount) of the polyol (b2) is usually 0.1 mass part or more and 250 mass parts or less, preferably 0.1 mass part or more and 210 mass parts or less, more preferably 0.1 mass part or more and 170 mass parts or less, further more preferably 0.5 mass part or more and 100 mass parts or less, further preferably 1 mass part or more and 50 mass parts or less, further preferably 1.5 mass parts or more and 45 mass parts or less, particularly preferably 1.7 mass parts or more and 42 mass parts or less.

[0133] By the content of polyol (b2) being above the above lower limit, the hardness of the cured film formed by the polyisocyanate being cured alone is low and the flexibility is better. In addition, an optical resin sheet having more excellent bonding strength, curability and bending resistance can be obtained. On the other hand, by the content of polyol (b2) being below the above upper limit, the flexibility when the polyisocyanate is manufactured can be maintained in a liquid state without gelation and forming an optical resin sheet is better.

[0134] The content of the polyol (b2) can be calculated from the blending amounts of the diisocyanate and the polyol (b2) during production of the polyisocyanate, for example.

[0135] In the aliphatic or alicyclic polyisocyanate (b), the content (charge amount) of the polyol (b3) is usually 0.1 parts by mass or more and 190 parts by mass or less, preferably 1 part by mass or more and 140 parts by mass or less, more preferably 1 part by mass or more and 90 parts by mass or less, further preferably 2 parts by mass or more and 80 parts by mass or less, further preferably 5 parts by mass or more and 70 parts by mass or less, further preferably 7 parts by mass or more and 65 parts by mass or less, particularly preferably 10 parts by mass or more and 60 parts by mass or less.

[0136] When the content of polyol (b3) is below the above upper limit, the curability and flexibility of the optical resin sheet can be better when the polyisocyanate is manufactured without gelation and the curability and flexibility of the optical resin sheet are better. On the other hand, when the content of polyol (b3) is above the above lower limit, the hardness of the cured film formed by curing the polyisocyanate alone is low and the flexibility is better. In addition, an optical resin sheet with better adhesion and curability can be obtained.

[0137] The content of the polyol (b3) can be calculated from the blending amounts of the diisocyanate and the polyol (b3) during production of the polyisocyanate, for example.

[0138] [Other crosslinking agent ingredients]

[0139] The crosslinking agent component (B) may contain, in addition to the above-mentioned aliphatic or alicyclic polyisocyanate (b), one or more other crosslinking agent components (b') selected from the group consisting of isocyanate compounds other than the aliphatic or alicyclic polyisocyanate (b), carbodiimide compounds, oxazoline compounds, polyfunctional acrylate monomers, peroxides, titanium coupling agents, zirconium compounds, metal aluminum chelates, hydrazide compounds, epoxy crosslinking agents, thermal acid generators and photoacid generators.

[0140] The content of the aliphatic or alicyclic polyisocyanate (b) in the crosslinking agent component (B) is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 90% by mass or more, and particularly preferably 100% by mass relative to the total mass of the crosslinking agent component (B). When the content of the aliphatic or alicyclic polyisocyanate (b) in the crosslinking agent component (B) is above the above lower limit, the effect of the optical resin composition of the present embodiment can be more fully exerted.

[0141] Examples of isocyanate compounds other than aliphatic or alicyclic polyisocyanates (b) include aliphatic or alicyclic diisocyanate monomers exemplified in the above diisocyanates (b1). In addition, examples include aromatic diisocyanates and triisocyanates exemplified in the above diisocyanates (b1), and polyisocyanates derived therefrom.

[0142] The carbodiimide compound can be obtained, for example, by subjecting the isocyanate groups of the polyisocyanate compound to a decarbonation reaction. Commercially available products of the carbodiimide compound include, for example, CARBODILITE V-02, CARBODILITE V-02-L2, CARBODILITE V-04, CARBODILITE E-01, and CARBODILITE E-02 (all manufactured by Nisshinbo Co., Ltd., trade names).

[0143] Examples of the oxazoline compound include a polymer compound having at least two oxazoline groups in a side chain and a monomer compound having at least two oxazoline groups in one molecule.

[0144] Examples of the polyfunctional acrylate monomer include tripentaerythritol acrylate, trimethylolpropane triacrylate, a condensate of pentaerythritol and acrylic acid, and 1,6-hexanediol diacrylate. The polyfunctional acrylate monomer referred to herein contains two or more vinyl groups and is distinguished from the above-mentioned crosslinkable functional group-containing monomer.

[0145] Examples of the peroxide include benzoyl peroxide, cumene hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, di-tert-butyl peroxide, tert-butylcumyl peroxide, di(2-tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, dicumyl peroxide, di-tert-butylperoxyisophthalate, tert-butylperoxybenzoate, 2,2-bis(tert-butylperoxy)butane, 2,2-bis(tert-butylperoxy)octane, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, bis(trimethylsilyl)peroxide, and trimethylsilyltriphenylsilyl peroxide.

[0146] Examples of the titanium coupling agent include isopropyl triisostearoyl titanate, isopropyl tri(dioctyl hydrogen phosphate) titanate, isopropyl tri(N-aminoethyl-aminoethyl) titanate, tetraoctyl bis(di-tridecyl phosphite) titanate, tetra(2,2-diallyloxymethyl-1-butyl)bis(di-tridecyl) phosphite titanate, bis(octyl hydrogen phosphate) oxyacetate titanate, bis(dioctyl hydrogen phosphate) ethylene titanate, isopropyl trioctanoyl titanate, isopropyl dimethacryloyl isostearyl titanate, isopropyl tri(dodecylbenzenesulfonyl) titanate, isopropyl isostearyl diacryl titanate, isopropyl tri(dioctyl sulfate) titanate, isopropyl tricumylphenyl titanate, and tetraisopropyl bis(dioctyl phosphite) titanate.

[0147] Examples of the zirconium compound include zirconium tetraacetylacetonate, zirconyl 2-ethylhexanoate, and zirconyl naphthenate.

[0148] Examples of the metal aluminum chelate include aluminum triacetylacetonate and the like.

[0149] Examples of the hydrazide compound include aliphatic carboxylic acid hydrazide, alicyclic carboxylic acid hydrazide, and aromatic carboxylic acid hydrazide.

[0150] Examples of the aliphatic carboxylic acid hydrazides and alicyclic carboxylic acid hydrazides include saturated or unsaturated fatty acid hydrazides such as lauric acid hydrazide, palmitic acid hydrazide, stearic acid hydrazide, adipic acid dihydrazide, sebacic acid dihydrazide, dodecanedioic acid dihydrazide, eicosanedioic acid dihydrazide, and sorbic acid hydrazide; hydroxy fatty acid hydrazides such as α-hydroxybutyric acid hydrazide and glyceric acid hydrazide; 7,11-octadecadiene-1,18-dicarbohydrazide, 1,3-bis(hydrazinocarbonylethyl)-5-isopropylhydantoin), tris(hydrazinocarbonylethyl)isocyanurate, and the like.

[0151] Examples of the aromatic carboxylic acid hydrazide include 1-naphthoic acid hydrazide, 2-naphthoic acid hydrazide, phthalic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, and 2,6-naphthoic acid dihydrazide.

[0152] Examples of the epoxy crosslinking agent include multifunctional epoxy resins such as "TETRAD-C" and "TETRAD-X" manufactured by Mitsubishi Gas Chemical Company, Inc.

[0153] Examples of the thermal acid generator include salts formed from a strong acid such as an onium salt having a function of generating an acid by heat and a base, and imide sulfonates.

[0154] Examples of the onium salt include diaryl iodonium salts such as aryldiazonium salts and diphenyliodonium salts; di(alkylaryl)iodonium salts such as di(tert-butylphenyl)iodonium salts; trialkylsulfonium salts such as trimethylsulfonium salts; dialkylmonoarylsulfonium salts such as dimethylphenylsulfonium salts; diarylmonoalkyliodonium salts such as diphenylmethylsulfonium salts; and triarylsulfonium salts.

[0155] In addition, as a salt formed by a strong acid and a base, in addition to the above-mentioned onium salts, a salt formed by the following strong acid and a base, such as a pyridinium salt, can also be used. Examples of strong acids include arylsulfonic acids such as p-toluenesulfonic acid and benzenesulfonic acid; perfluoroalkylsulfonic acids such as camphorsulfonic acid, trifluoromethanesulfonic acid, and nonafluorobutanesulfonic acid; alkylsulfonic acids such as methanesulfonic acid, ethanesulfonic acid, and butanesulfonic acid. Examples of bases include pyridine; alkylpyridines such as 2,4,6-trimethylpyridine; N-alkylpyridines such as 2-chloro-N-methylpyridine; and halogenated-N-alkylpyridines.

[0156] Examples of the imide sulfonate include naphthimide sulfonate and phthalimide sulfonate, but the imide sulfonate is not limited as long as it is a compound that generates an acid by heat.

[0157] As the photoacid generator, a photoacid generator that generates an acid capable of cation polymerization by ultraviolet irradiation is used, and the reaction is further promoted by applying heat. Examples of such photoacid generators include SbF 6 -PF6 -、BF 4 -、AsF 6 -、(C 6 F 5 ) 4 -PF 4 (CF 2 CF 3 ) 2 - and anion components such as onium salts of cationic components (diazonium salts, sulfonium salts, iodonium salts, selenium salts, pyridinium salts, ferrocerium salts, phosphonium salts, etc.). They are used alone or in combination of two or more. Specifically, for example, aromatic sulfonium salts, aromatic iodonium salts, aromatic phosphonium salts, aromatic sulfonium oxide salts, etc. can be listed.

[0158] [Method for producing cross-linking agent component (B)]

[0159] When the crosslinking agent component (B) is an aliphatic or alicyclic polyisocyanate (b), it is obtained by reacting the above-mentioned diisocyanate (b1), polyol (b2), and polyol (b3).

[0160] The polyol (b2) and the polyol (b3) may be used alone or in a mixture. When used in a mixture, they may be mixed before reacting with diisocyanate, or each polyol may be reacted with diisocyanate alone to form a polyisocyanate and then mixed.

[0161] That is, examples of methods for producing polyisocyanates include a method in which a diisocyanate, a polyol (b2), and a polyol (b3) are reacted simultaneously to obtain a polyisocyanate; a method in which a product obtained by reacting a diisocyanate with a polyol (b2) and a product obtained by reacting a diisocyanate with a polyol (b3) are mixed to obtain a polyisocyanate; a method in which a diisocyanate is reacted with a polyol (b2) or a polyol (b3) and then reacted with the remaining polyol to obtain a polyisocyanate; and the like.

[0162] The amounts of the polyol (b2) and the polyol (b3) added are preferably such that the mass ratio of the polyol (b2) to the polyol (b3) falls within the above range.

[0163] During the reaction, the molar ratio of the isocyanate group of the diisocyanate to the hydroxyl group of the polyol (b2) and the polyol (b3) (molar ratio of isocyanate group / hydroxyl group) is preferably 3 or more and 30 or less, more preferably 4 or more and 25 or less, further preferably 5 or more and 22 or less, and particularly preferably 6 or more and 20 or less. When the NCO / OH ratio is within the above numerical range, the crosslinking agent component (B) can be synthesized without gelation, and the elastic modulus, elongation, and breaking strength of the obtained optical resin sheet can be further reduced.

[0164] The reaction of the polyol and the diisocyanate is carried out as follows. The reaction temperature is usually above room temperature (about 23°C) and below 200°C, preferably above 60°C and below 130°C. If the reaction temperature is above the lower limit, the reaction time is further shortened. On the other hand, if it is below the upper limit, the viscosity increase of the polyisocyanate caused by the unpreferable side reaction can be further avoided, and the coloring of the generated polyisocyanate can be further avoided.

[0165] The reaction may be carried out without a solvent or using any solvent inactive to isocyanate groups. In addition, a known catalyst may be used to promote the reaction between the isocyanate groups and the hydroxyl groups as required.

[0166] [Physical properties of cross-linking agent component (B)]

[0167] The isocyanate group content (NCO group content) of the crosslinking agent component (B) is preferably from 1% by mass to 10% by mass, more preferably from 2% by mass to 9% by mass, further preferably from 2.5% by mass to 8.5% by mass, particularly preferably from 2.7% by mass to 8.2% by mass, relative to the total mass of the crosslinking agent component (B), in a state where a solvent and a diisocyanate are substantially not contained.

[0168] The NCO group content can be determined, for example, by reacting the isocyanate groups in the crosslinking agent component (B) with an excess of amine (dibutylamine or the like), and then back-titrating the excess amine with an acid such as hydrochloric acid.

[0169] When only the crosslinking agent component (B) is applied on glass and stored at 23°C and 65% humidity for 168 hours, a cured film having a film thickness of 40 μm formed by the reaction of moisture in the film with the polyisocyanate composition has a pendulum hardness of 60 times or less, preferably 57 times or less, more preferably 55 times or less, and further preferably 54 times or less, at 23°C. When the pendulum hardness is below the upper limit, the hardness is low and the flexibility is more excellent.

[0170] [Content of cross-linking agent component (B)]

[0171] The content of the crosslinking agent component (B) is preferably 0.01 mass parts or more and 5.00 mass parts or less relative to 100 mass parts of acrylic polymer (A), more preferably 0.03 mass parts or more and 4.00 mass parts or less, further preferably 0.05 mass parts or more and 3.50 mass parts or less, particularly preferably 0.07 mass parts or more and 3.00 mass parts or less. By the content of the crosslinking agent component (B) being within the above numerical range, there is a tendency that the curability when forming the optical resin sheet is more excellent, the bending resistance, the adhesive force and the holding power are more excellent. The content of the crosslinking agent component (B) can be calculated, for example, by the compounding amount of the crosslinking agent component (B) used in the manufacture of the optical resin composition.

[0172] [Isocyanate group / crosslinking functional group]

[0173] The molar ratio of the isocyanate group of the crosslinking agent component (B) to the crosslinkable functional group (especially hydroxyl group) of the acrylic polymer (A) (molar ratio of isocyanate group / crosslinkable functional group) contained in the optical resin composition of the present embodiment is determined by the desired physical properties of the optical resin sheet and is usually greater than or equal to 0.01 and less than or equal to 50.

[0174] <Other ingredients>

[0175] The optical resin composition of the present embodiment may further contain 0.01 to 0.5 parts by mass of a silane coupling agent (C) relative to 100 parts by mass of the acrylic polymer (A). The optical resin composition of the present embodiment further improves the adhesive force of the optical resin sheet obtained by containing the silane coupling agent (C) in an amount within the above numerical range, and can further suppress the activity and peeling of the adherend interface during heating and humidification.

[0176] The silane coupling agent (C) is not limited to the following, and examples thereof include 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, ureidepropyltriethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, methyltriethoxysilane, and methyltrimethoxysilane.

[0177] The content of the silane coupling agent (C) is preferably 0.01 parts by mass or more and 0.5 parts by mass or less, and more preferably 0.05 parts by mass or more and 0.4 parts by mass or less, based on 100 parts by mass of the acrylic polymer (A).

[0178] The optical resin composition of the present embodiment may further contain other additives.

[0179] Other additives include, for example, curing catalysts, solvents, pigments (extender pigments, coloring pigments, metallic pigments, etc.), tackifying resins, photopolymerization initiators, ultraviolet absorbers, light stabilizers, free radical stabilizers, anti-yellowing agents for suppressing coloration during the sintering process, coating surface regulators, flow regulators, pigment dispersants, defoaming agents, thickeners, film-forming aids, and the like.

[0180] The curing catalyst may be a basic compound or a Lewis acid compound.

[0181] Examples of the basic compound include metal hydroxides, metal alkoxides, metal carboxylates, metal acetylacetonates, hydroxides of onium salts, onium carboxylates, halides of onium salts, metal salts of active methylene compounds, onium salts of active methylene compounds, aminosilanes, amines, phosphines, etc. The onium salt is preferably an ammonium salt, a phosphonium salt or a sulfonium salt.

[0182] Examples of the Lewis acidic compound include organic tin compounds, organic zinc compounds, organic titanium compounds, and organic zirconium compounds.

[0183] Examples of the solvent include 1-methylpyrrolidone, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, dipropylene glycol monomethyl ether, propylene glycol monomethyl ether, 3-methoxy-3-methyl-1-butanol, ethylene glycol diethyl ether, diethylene glycol diethyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dipropylene glycol dimethyl ether (DPDM), propylene glycol dimethyl ether, methyl ethyl ketone, Acetone, methyl isobutyl ketone, propylene glycol monomethyl ether acetate, ethanol, methanol, isopropanol, 1-propanol, isobutyl alcohol, 1-butanol, tert-butyl alcohol, 2-ethylhexanol, cyclohexanol, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, ethyl acetate, isopropyl acetate, butyl acetate, toluene, xylene, pentane, isopentane, hexane, isohexane, cyclohexane, solvent naphtha, mineral spirits, etc. These solvents may be used alone or in combination of two or more.

[0184] In addition, known additives may be appropriately selected and used as pigments (extenders, coloring pigments, metallic pigments, etc.), ultraviolet absorbers, light stabilizers, free radical stabilizers, anti-yellowing agents for suppressing coloration during the sintering process, coating surface regulators, flow regulators, pigment dispersants, defoamers, thickeners, and film-forming aids.

[0185] <Method for producing optical resin composition>

[0186] The optical resin composition can be produced by a conventionally known method, for example, a melt kneading method using a Banbury mixer, a single screw extruder, a twin screw extruder, a co-kneader, a multi-screw extruder or the like; a method in which each component is dissolved or dispersed and mixed, and then applied to a substrate film by a coater, and then the solvent is removed by heating.

[0187] 《Optical resin sheet》

[0188] The optical resin sheet of the present embodiment is obtained by curing the above-mentioned optical resin composition with heat or light.

[0189] The optical resin sheet of the present embodiment has good transparency, and is excellent in adhesive strength, holding power, and bending resistance.

[0190] The thickness of the optical resin sheet of the present embodiment can be appropriately determined depending on the intended use, but is preferably 1 μm to 1000 μm, more preferably 3 μm to 900 μm, further preferably 5 μm to 800 μm, and particularly preferably 7 μm to 700 μm.

[0191] The optical resin sheet of the present embodiment can be produced, for example, by applying the above-mentioned optical resin composition on a substrate, drying it as necessary, and then curing it.

[0192] The substrate is not particularly limited, and examples thereof include papers such as high-quality paper, coated paper, cast-coated paper, thermal paper, and inkjet paper; fabrics such as woven fabrics and nonwoven fabrics; resin films such as polyvinyl chloride, synthetic paper, polyethylene terephthalate (PET), polypropylene, polyethylene, cellulose triacetate, cellulose diacetate, polystyrene, polycarbonate, nylon, polyvinyl alcohol, ethylene-vinyl acetate copolymer, and polyimide; porous resin films such as porous polypropylene films; vapor-deposited films formed by vapor-depositing aluminum or the like on PET, polyolefins, etc.; metal foils, etc. The substrate may also be a substrate on which a release treatment has been applied to the surface.

[0193] As a method for coating the optical resin composition on the substrate, for example, a coating method using an applicator, a roll coater, a knife coater, a gravure coater, etc. can be cited. In the case of drying after the above coating, for example, a heating drying method can be cited, for example, in which the obtained laminate is loaded into a dryer, for example, at a temperature of 50° C. to 150° C., and dried for 1 minute to 30 minutes. Alternatively, as other drying methods, for example, natural drying, hot air drying, infrared drying, etc. can be cited.

[0194] The heating temperature during curing may be 70° C. or higher and 150° C. or lower, 75° C. or higher and 145° C. or lower, or 80° C. or higher and 140° C. or lower.

[0195] The optical resin sheet of the present embodiment is laminated to a SUS304BA plate as an adherend, and after being pressed back and forth once with a 2 kg roller and aged at 23° C. for 30 minutes, the 180-degree peeling adhesive strength measured at 23° C. and a speed of 300 mm / min is preferably 2.0 N / 20 mm or more and 65 N / 20 mm or less, more preferably 4.0 N / 20 mm or more and 63 N / 20 mm or less, and further preferably 5.0 N / 20 mm or more and 6.5 N / 20 mm or less. The optical resin sheet is an optical resin sheet having a thickness of 70 μm, a width of 20 mm and a length of 100 mm obtained by coating the optical resin composition on a polyethylene terephthalate film having a thickness of 25 μm, drying at 125° C. for 3 minutes to cure, and then storing the sheet under 23° C. and 50% RH for 7 days. The 180-degree peeling adhesive strength is above the above lower limit, and the adhesive strength is more excellent.

[0196] For the optical resin sheet of the present embodiment, the following optical resin sheet is attached to a SUS304BA plate as an adherend in an overlapping manner with a width of 25 mm and a length of 25 mm, and is reciprocated and pressed once with a 2 kg roller and aged at 23° C. for 1 hour, and further aged at 40° C. for 30 minutes, and then a 500 g weight is hung at the lower end of the optical resin sheet at 40° C. for 1 hour, and then the offset of the optical resin sheet when it is restored to 23° C. is preferably 2 (mm / hour) or less. , more preferably 1 (mm / hour) or less, further preferably 0.5 (mm / hour) or less, particularly preferably 0.3 (mm / hour) or less, the optical resin sheet is: the optical resin composition is coated on a polyethylene terephthalate film with a thickness of 25 μm, dried at 125°C for 3 minutes to cure, and then stored at 23°C, 50% RH for 7 days to obtain an optical resin sheet with a thickness of 70 μm, a width of 25 mm, and a length of 130 mm on one side of the polyethylene terephthalate film. By making the offset amount below the above upper limit, the holding force (cohesion force) is more excellent.

[0197] The lower limit of the deviation amount is preferably as small as possible, and may be, for example, 0.0 (mm / hour).

[0198] For the optical resin sheet of this embodiment, the following optical resin sheet is pasted on a glass with a haze value of 0.1%, and the haze value measured by a haze meter is preferably 2.0% or less, more preferably 1.0% or less, further preferably 0.9% or less, and particularly preferably 0.8% or less. The optical resin sheet is: the above-mentioned optical resin composition is applied on a polyethylene terephthalate film with a thickness of 38 μm and subjected to a peeling treatment, and after drying at 125°C for 3 minutes to cure, it is stored at 23°C and 50% RH for 7 days, and the optical resin sheet with a thickness of 70 μm is obtained by peeling it from the above-mentioned polyethylene terephthalate film that has been peeled off.

[0199] The lower limit of the haze value is preferably as small as possible, and may be, for example, 0.1%.

[0200] The optical resin sheet of the present embodiment is stored at 23°C and 50% RH for 7 days, wrapped in a mesh sheet, immersed in ethyl acetate at 23°C for 1 week, taken out and dried at 120°C for 2 hours. The gel fraction calculated is preferably 40.0% by mass or more and 99.9% by mass or less, more preferably 55.0% by mass or more and 99.9% by mass or less, further preferably 58.0% by mass or more and 99.9% by mass or less, and particularly preferably 62.0% by mass or more. The optical resin sheet is prepared by coating the optical resin composition on a polyethylene terephthalate film having a thickness of 38 μm and undergoing a peeling treatment, drying the film at 125° C. for 3 minutes to cure the film, and then storing the film at 23° C. and 50% RH for 7 days. The optical resin sheet having a thickness of 70 μm obtained by peeling the polyethylene terephthalate film having a peeling treatment has a gel fraction of more than the above lower limit, and has better curing properties, cohesiveness, and moisture-heat resistance.

[0201] The gel fraction referred to herein is a percentage of the mass of the optical resin sheet after being immersed in ethyl acetate and then dried relative to the mass of the optical resin sheet before being immersed in ethyl acetate.

[0202] The optical resin sheet of the present embodiment is stacked in a manner of 210 μm in thickness, cut into pieces of 10 mm in width and 40 mm in length, and then mounted on a tensile testing machine with a distance between chucks of 10 mm. The Young's modulus in a tensile test performed at a speed of 300 mm / min at 23° C. is preferably 0.40 N / mm 2 Less than, more preferably 0.30N / mm 2 Below, more preferably 0.25N / mm 2 Below, particularly preferably 0.20 N / mm 2 Hereinafter, the optical resin sheet is a 70 μm thick optical resin sheet obtained by coating the optical resin composition on a 38 μm thick polyethylene terephthalate film subjected to a peeling treatment, drying at 125° C. for 3 minutes to cure, and then storing at 23° C. and 50% RH for 7 days, and peeling from the polyethylene terephthalate film subjected to the peeling treatment. When the Young's modulus is below the above upper limit, the flexibility, adhesive strength and bending resistance are more excellent.

[0203] The lower limit of the Young's modulus is preferably as small as possible, and may be, for example, 0.01 N / mm 2 , can be 0.02N / mm 2 .

[0204] As described above, the optical resin sheet of the present embodiment has good transparency and is excellent in adhesive strength, holding power, and bending resistance, and therefore is preferably used as, for example, an optical transparent adhesive sheet (OCA).

[0205] Example

[0206] The present invention will be described below by way of examples, but the present invention is not limited to the following examples.

[0207] [Physical properties 1]

[0208] (Glass transition temperature Tg)

[0209] The glass transition temperature of the acrylic polymer (A) is obtained by blowing off the organic solvent and water in a solution of the acrylic polymer (A) under reduced pressure and then vacuum drying the solution, using a differential scanning calorimeter (DSC) measuring apparatus, at a temperature increase rate of 5°C / min. The value obtained is used as the glass transition temperature.

[0210] [Physical Properties 2]

[0211] (Number average molecular weight and weight average molecular weight)

[0212] The number average molecular weight and the weight average molecular weight are those based on polystyrene measured by gel permeation chromatography (GPC) using the following apparatus.

[0213] (Measurement conditions)

[0214] Device: Made by TOSOH CORPORATION, HLC-802A

[0215] Chromatographic column: Made by TOSOH CORPORATION, G1000HXL x 1

[0216] G2000HXL×1

[0217] G3000HXL×1

[0218] Carrier: Tetrahydrofuran

[0219] Detection method: Differential refractometer

[0220] [Physical Properties 3]

[0221] (Isocyanate group content)

[0222] First, accurately weigh more than 2g and less than 3g (Wg) of the test sample in a flask. Then add 20mL of toluene to dissolve the test sample. Then add 20mL of 2N di-n-butylamine toluene solution and mix, and leave at room temperature for 15 minutes. Then add 70mL of isopropanol and mix. Then titrate the liquid with a 1N hydrochloric acid solution (factor F) using an indicator. The titration value obtained is V2mL. Then, in the absence of a sample, the titration value obtained is V1ml. Then calculate the isocyanate group content (NCO%) (mass %) of the crosslinking agent component (B) by the following formula.

[0223] "Isocyanate group content (mass %)" = (V1-V2) × F × 42 / (W × 1000) × 100

[0224] [Physical Properties 4]

[0225] (Average number of isocyanate functional groups)

[0226] The average number of isocyanate functional groups (average number of NCO) of the crosslinking agent component (B) is calculated by the following formula. It should be noted that in the formula, "Mn" refers to the number average molecular weight, and the value measured in the above "Physical Property 2" is used. "NCO%" uses the value calculated in the above "Physical Property 3".

[0227] Average number of isocyanate functional groups = (Mn × NCO% × 0.01) / 42

[0228] [Preparation of Cured Film of Crosslinking Agent Component (B)]

[0229] Each crosslinking agent component (B) was applied onto a glass using an applicator and stored in an environment of 23° C. and 65% humidity for 168 hours to obtain a cured film having a film thickness of 40 μm.

[0230] [Property 5]

[0231] (Pendulum hardness)

[0232] The pendulum hardness (times) of each cured film in a 23° C. environment was measured using a pendulum hardness tester (Pendulum hardness tester manufactured by BYK Gardner).

[0233] <Evaluation Method>

[0234] [Production of Optical Resin Sheet 1]

[0235] Each optical resin composition was applied onto a polyethylene terephthalate (PET) film having a thickness of 25 μm using an applicator so as to have a thickness of 70 μm after drying, and dried at 125° C. for 3 minutes. The film was then stored at 23° C. and 50% RH for 7 days for 180-degree peeling adhesive strength measurement and holding strength measurement, thereby obtaining an optical resin sheet 1 having a PET film on one side.

[0236] [Production of Optical Resin Sheet 2]

[0237] Each optical resin composition was applied to a 38 μm thick release-treated PET film using an applicator so that the thickness after drying was 70 μm, and dried at 125° C. for 3 minutes. Then, the optical resin sheet 2 having a release-treated PET film on one side was obtained for gel fraction measurement, haze measurement, and tensile test by storing it at 23° C. and 50% RH for 7 days. The release-treated PET film was peeled off and used for each evaluation.

[0238] [Evaluation 1]

[0239] (180 degree peel adhesion)

[0240] The optical resin sheet 1 obtained in the above "Preparation of the optical resin sheet 1" was cut into a width of 20 mm and a length of 100 mm to obtain a test piece. The test piece was then bonded to a SUS304BA plate as an adherend, and a 2 kg roller was reciprocated once to press the test piece onto the SUS304BA plate. After aging at 23°C for 30 minutes, a tensile tester was used to measure the 180 degree peeling adhesive strength at a speed of 300 mm / min.

[0241] The case of 2.0 N / 20 mm or more was evaluated as good adhesive force.

[0242] [Evaluation 2]

[0243] (Retention force)

[0244] The optical resin sheet 1 obtained in the above "Production of the optical resin sheet 1" was cut into pieces with a width of 25 mm and a length of 130 mm to obtain a test piece. The test piece was then pasted to a SUS304BA plate as an adherend in a manner overlapping a width of 25 mm and a length of 25 mm, and was reciprocated and pressed once with a 2kg roller and aged at 23°C for 30 minutes, and further aged at 40°C for 1 hour. A 500g weight was then hung at the lower end of the test piece at 40°C for 1 hour, and the test piece was returned to a 23°C environment, and the offset (mm / hour) of the test piece at this time was measured.

[0245] There is a tendency that the smaller the deviation amount is, the better the holding force (cohesion force) is. When the deviation amount is 0.5 (mm / hour) or less, the holding force (cohesion force) is evaluated to be good.

[0246] [Evaluation 3]

[0247] (Haze)

[0248] The optical resin sheet 2 obtained in the above "Preparation of the optical resin sheet 2" was bonded to a glass having a haze value of 0.1%, and peeled off from the polyethylene terephthalate film subjected to the peeling treatment to prepare a test piece. Next, the haze of the test piece was measured using a haze meter (HMG-2DP) manufactured by Suga Test Instruments Co., Ltd., on one side of the two sides of the test piece where the light source was arranged and the polyethylene terephthalate film subjected to the peeling treatment was peeled off.

[0249] When the haze value was 1.0% or less, the transparency was evaluated to be good.

[0250] [Evaluation 4]

[0251] (Gel fraction)

[0252] The optical resin sheet 2 obtained in the above "Preparation of the optical resin sheet 2" and from which the PET film subjected to the peeling treatment was peeled off was collected in an amount of about 0.1 g or more and about 0.2 g or less, wrapped in a mesh sheet, immersed in ethyl acetate for 1 week, and then dried at 120° C. for 2 hours. Then, the gel fraction (mass %) was calculated using the following formula.

[0253] When the gel fraction was 60% by mass or more, the curability was evaluated to be good.

[0254] (Gel fraction) = (mass of sample after being put into ethyl acetate and dried) / (mass of sample before being put into ethyl acetate) × 100

[0255] [Evaluation 5]

[0256] (Tensile test: Young's modulus, elongation, maximum stress and strain energy indicators)

[0257] The optical resin sheet 1 obtained in the above "Preparation of the optical resin sheet 1" and the PET film subjected to the peeling treatment was peeled off was stacked in a manner of 210 μm in thickness and cut into 10 mm in width and 40 mm in length. Then, it was installed in a tensile tester in a manner of 10 mm between chucks, and the Young's modulus, elongation and maximum stress were measured at a speed of 300 mm / min using the tensile tester under a 23°C environment. Then, the strain energy index was calculated using the following formula from the obtained elongation and maximum stress.

[0258] For Young's modulus, it is 0.25N / mm 2 When the strain energy index was 2.00 or more, the bending resistance was evaluated to be good.

[0259] (Strain energy index) = {(elongation (%)) / 100) × (maximum stress)} × 1 / 2

[0260] <Synthesis of acrylic polymer (A)>

[0261] [Synthesis Example 1-1]

[0262] (Synthesis of Acrylic Polymer A-1)

[0263] In a four-necked flask equipped with a stirrer, a thermometer, a nitrogen inlet tube, and a cooling tube, 97 parts by mass of 2-ethylhexyl acrylate (2EHA), 3 parts by mass of 4-hydroxybutyl acrylate (4HBA), and 140 parts by mass of ethyl acetate as a solvent were added. Then, 0.15 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator was added while stirring under a nitrogen atmosphere, and the reaction was carried out at 63°C for 8 hours. After the reaction, the mixture was cooled to obtain an acrylic polymer A-1 having a solid content concentration of 42.0% by mass.

[0264] [Synthesis Examples 1-2 to 1-14]

[0265] (Synthesis of Acrylic Polymers A-1 to A-14)

[0266] Each acrylic polymer was synthesized by the same method as Synthesis Example 1-1 except that the blending ratio of each monomer was as described in Tables 1 and 2.

[0267] The composition and physical properties of each synthesized acrylic polymer are shown in the following Tables 1 and 2. In addition, in Tables 1 and 2, the abbreviations of monomers represent the following compounds.

[0268] (Crosslinkable functional group-containing monomer (a1))

[0269] 4HBA: 4-Hydroxybutyl acrylate

[0270] HEA: Hydroxyethyl acrylate

[0271] AA: Acrylic acid

[0272] ((Meth)acrylate monomer (a2))

[0273] 2EHA: 2-Ethylhexyl acrylate

[0274] MEA: Methoxyethyl acrylate

[0275] iOA: Isooctyl acrylate

[0276] iNA: Isononyl acrylate

[0277] EA: Ethyl acrylate

[0278] MA: Methyl acrylate

[0279] BezA: Benzyl acrylate

[0280] BA: Butyl acrylate

[0281] PEA: Phenoxyethyl acrylate

[0282] (Other polymerizable monomers (a3))

[0283] NVP: N-vinyl-2-pyrrolidone

[0284] [Table 1]

[0285]

[0286] [Table 2]

[0287]

[0288] <Synthesis of cross-linking agent component (B)>

[0289] [Synthesis example 2-1]

[0290] (Synthesis of polyisocyanate component B-1)

[0291] In a four-necked flask equipped with a thermometer, a stirring blade and a reflux cooling tube, 100 parts by mass of HDI, 4.7 parts by mass of a bifunctional polycaprolactone polyol (manufactured by Daicel Corporation, trade name "PLACCEL 220", number average molecular weight 2000) (hereinafter sometimes referred to as "polyol b2-1" or simply "b2-1"), and 33 parts by mass of a trifunctional polycaprolactone polyol (manufactured by Daicel Corporation, trade name "PLACCEL 308", number average molecular weight 850) (hereinafter sometimes referred to as "polyol b3-1" or simply "b3-1") (an amount in which the molar ratio of the isocyanate group of HDI to the hydroxyl group of the polyol b2-1 and the polyol b3-1 is 10.0) were added under a nitrogen stream, while stirring, the temperature in the reactor was kept at 90° C. for 110 minutes or more, and the reaction was stopped when the yield reached 40% by mass. After filtering the reaction liquid, unreacted HDI was removed using a thin film distillation apparatus to obtain a polyisocyanate component B-1.

[0292] [Synthesis Examples 2-2 to 2-6]

[0293] (Synthesis of polyisocyanate components B-2 to B-6)

[0294] The types and blending ratios of the raw materials were as described in Table 3, and each polyisocyanate component was synthesized by the same method as in Synthesis Example 2-1.

[0295] [Synthesis example 2-7]

[0296] (Synthesis of polyisocyanate component B-7)

[0297] In a four-necked flask equipped with a thermometer, a stirring blade and a reflux cooling tube, 100 parts by mass of HDI and 8.9 parts by mass of trimethylolpropane (hereinafter sometimes referred to as "polyol b3-3" or simply "b3-3") were added under a nitrogen stream, and the temperature in the reactor was kept at 75°C for 5 hours under stirring to carry out a urethanization reaction. After filtering the reaction liquid, unreacted HDI was removed using a thin film evaporator to obtain an isocyanurate type polyisocyanate (hereinafter sometimes referred to as "polyisocyanate component B-7").

[0298] [Synthesis example 2-8]

[0299] (Synthesis of polyisocyanate component B-8)

[0300] In a four-necked flask equipped with a thermometer, a stirring blade and a reflux cooling tube, 100 parts by mass of HDI was added under a nitrogen flow, the temperature in the reactor was kept at 62°C under stirring, 0.095 parts by mass of trimethylbenzyl ammonium hydroxide was added, and the reaction was allowed to proceed for 4 hours. Then, when the conversion rate reached 38% by mass, 0.02 parts by mass of phosphoric acid was added to stop the reaction. After filtering the reaction solution, unreacted HDI was removed using a thin film evaporator to obtain an isocyanurate type polyisocyanate (hereinafter sometimes referred to as "polyisocyanate component B-8").

[0301] [Synthesis example 2-9]

[0302] (Synthesis of polyisocyanate component B-9)

[0303] In a four-necked flask equipped with a thermometer, a stirring blade and a reflux cooling tube, 100 parts by mass of HDI and 30 parts by mass of polyol b3-1 (the molar ratio of the isocyanate group of HDI to the hydroxyl group of polyol b3-1 is 11.4) were added under a nitrogen stream, and the temperature in the reactor was kept at 95°C for 80 minutes. The reaction was stopped at a yield of 39% by mass. After filtering the reaction solution, unreacted HDI was removed by a thin film distillation apparatus to obtain polyisocyanate component B-9.

[0304] [Synthesis example 2-10]

[0305] (Synthesis of polyisocyanate component B-10)

[0306] In a four-necked flask equipped with a thermometer, a stirring blade and a reflux cooling tube, 100 parts by mass of HDI was added under a nitrogen stream, and 22.0 parts by mass of a trifunctional polycaprolactone polyol (hereinafter sometimes referred to as "polyester polyol b3-3") (manufactured by Daicel Corporation, trade name "PLACCEL 305", number average molecular weight 550) (the molar ratio of the isocyanate group of HDI to the hydroxyl group of the polyol was 9.9) was stirred, while the temperature in the reactor was maintained at 90°C for 75 minutes. The reaction was stopped at a yield of 33% by mass. After filtering the reaction solution, unreacted HDI was removed by a thin film distillation apparatus to obtain a polyisocyanate component B-10.

[0307] The compositions and physical properties of the synthesized polyisocyanate components are shown in the following Table 3. In addition, in Table 3, the polyols are the following compounds.

[0308] (Polyol (b2))

[0309] b2-1: bifunctional polycaprolactone polyol, manufactured by Daicel Corporation, trade name "PLACCEL 220", number average molecular weight 2000

[0310] (Polyol (b2'))

[0311] b2'-1: polyether polyol, manufactured by Asahi Glass Co., Ltd., trade name "Excenol 2020", number average molecular weight 2000

[0312] (Polyol (b3))

[0313] b3-1: trifunctional polycaprolactone polyol, manufactured by Daicel Corporation, trade name "PLACCEL 308", number average molecular weight 850

[0314] b3-2: trifunctional polycaprolactone polyol, manufactured by Daicel Corporation, trade name "PLACCEL 312", number average molecular weight 1250

[0315] b3-3: trifunctional polycaprolactone polyol, manufactured by Daicel Corporation, trade name "PLACCEL 305", number average molecular weight 550

[0316] (Polyol (b3'))

[0317] b3'-1: Trimethylolpropane (TMP)

[0318] [Table 3]

[0319]

[0320] <Production of optical resin composition>

[0321] [Example 1]

[0322] (Production of Optical Resin Composition O-a1)

[0323] With respect to 100 parts by mass of acrylic polymer A-1, 0.5 parts by mass of polyisocyanate component B-1, 0.1 parts by mass of silane coupling agent (3-glycidoxypropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM-403"), and ethyl acetate were added to obtain an optical resin composition O-a1 having a solid content of 30% by mass.

[0324] [Examples 2 to 14 and Comparative Examples 1 to 5]

[0325] (Manufacture of optical resin compositions O-a2 to O-a14 and O-b1 to O-b5)

[0326] Each optical resin composition was produced by the same method as in Example 1 except that the types and blending ratios of the acrylic polymer (A) and the crosslinking agent component (B) were as described in Tables 4 to 6.

[0327] The composition and evaluation results of each optical resin composition are shown in Tables 4 to 6.

[0328] [Table 4]

[0329]

[0330] [Table 5]

[0331]

[0332] [Table 6]

[0333]

[0334] As can be seen from Tables 4 to 6, the optical resin sheets formed using the optical resin compositions O-a1 to O-a14 (Examples 1 to 14) have good transparency and are excellent in adhesion, holding power and bending resistance. The optical resin compositions O-a1 to O-a14 contain an acrylic polymer (A) having a glass transition temperature Tg of not less than -69.7°C and not more than -58.0°C, a monomer containing a crosslinkable functional group, and a (meth)acrylate monomer having a carbon number at the end of the ester group within a specific numerical range; and an aliphatic polyisocyanate having a weight average molecular weight of not less than 4180 and not more than 32700 and an average number of isocyanate groups of not less than 3.8 and not more than 5.0 as a crosslinking agent component (B).

[0335] On the other hand, the optical resin sheets formed using the optical resin compositions O-b1, O-b3, O-b4 and O-b5 (Comparative Examples 1, 3, 4 and 5) have good transparency, holding power and adhesive strength, but poor bending resistance. The optical resin compositions O-b1, O-b3, O-b4 and O-b5 each contain 0.5 parts by mass of polyisocyanate components B-7 to B-9 having a weight average molecular weight of less than 1400 as a crosslinking agent component (B) based on 100 parts by mass of the acrylic polymer (A).

[0336] In addition, for the optical resin sheet formed by using the optical resin composition O-b2 (Comparative Example 2), although the transparency and adhesive force are good, the holding force and bending resistance are poor. The optical resin composition O-b2 contains 0.05 mass parts of polyisocyanate component B-7 with a weight average molecular weight of less than 1400 as the crosslinking agent component (B).

[0337] Industrial Applicability

[0338] According to the optical resin composition of this embodiment, it is possible to provide an optical resin composition that maintains good transparency when forming an optical resin sheet and has excellent adhesive force, holding power and bending resistance. The optical resin sheet of the above embodiment is formed by curing the above optical resin composition, has good transparency, and has excellent adhesive force, holding power and bending resistance.

Claims

1. An optical resin composition comprising an acrylic polymer (A) and a crosslinking agent component (B), The acrylic polymer (A) is obtained by copolymerizing a monomer containing a crosslinkable functional group and a (meth)acrylate monomer having a carbon number of 1 to 18 at the end of the ester group. The glass transition temperature Tg of the acrylic polymer (A) is -10.0°C or lower, The crosslinking agent component (B) contains an aliphatic or alicyclic polyisocyanate having a weight average molecular weight of 2,800 or more and 200,000 or less, The average number of isocyanate groups of the crosslinking agent component (B) is 3.8 or more and 6.5 or less, The content of the crosslinking agent component (B) is 0.01 parts by mass or more and 5.0 parts by mass or less relative to 100 parts by mass of the acrylic polymer (A).

2. The optical resin composition according to claim 1, wherein The glass transition temperature Tg of the acrylic polymer (A) is -75.0°C or higher and -10.0°C or lower.

3. The optical resin composition according to claim 1 or 2, wherein The glass transition temperature Tg of the acrylic polymer (A) is -71.0°C or higher and -50.0°C or lower.

4. The optical resin composition according to claim 1 or 2, wherein The weight average molecular weight of the aliphatic or alicyclic polyisocyanate is 2,800 or more and 150,000 or less.

5. The optical resin composition according to claim 1 or 2, wherein The weight average molecular weight of the aliphatic or alicyclic polyisocyanate is 3,200 or more and 70,000 or less.

6. The optical resin composition according to claim 1 or 2, wherein The average number of isocyanate groups of the crosslinking agent component (B) is 3.8 or more and 6.0 or less.

7. The optical resin composition according to claim 1 or 2, wherein The content of the crosslinking agent component (B) is 0.07 parts by mass or more and 3.00 parts by mass or less relative to 100 parts by mass of the acrylic polymer (A).

8. The optical resin composition according to claim 1 or 2, wherein The weight average molecular weight of the acrylic polymer (A) is 5.0×10 5 Above and 5.0×10 6 the following.

9. The optical resin composition according to claim 1 or 2, wherein The weight average molecular weight of the acrylic polymer (A) is 6.0×10 5 Above and 2.5×10 6 the following.

10. The optical resin composition according to claim 1 or 2, wherein The weight average molecular weight of the acrylic polymer (A) is 7.0×10 5 Above and 1.9×10 6 the following.

11. The optical resin composition according to claim 1 or 2, wherein The crosslinkable functional group is one or more selected from the group consisting of a hydroxyl group, an epoxy group, a carboxyl group, and a vinyl group.

12. The optical resin composition according to claim 1 or 2, wherein The content of the structural unit derived from the crosslinkable functional group-containing monomer is 0.01% by mass or more and 25% by mass or less based on the total mass of the acrylic polymer (A).

13. The optical resin composition according to claim 1 or 2, wherein The content of the structural unit derived from the (meth)acrylate monomer is 0.01% by mass or more and 99.99% by mass or less based on the total mass of the acrylic polymer (A).

14. The optical resin composition according to claim 1 or 2, wherein The aliphatic or alicyclic polyisocyanate is a polyisocyanate derived from at least one diisocyanate (b1) selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates, a bifunctional polyol (b2) having a number average molecular weight of 1500 or more, and a trifunctional or higher polyol (b3) having a number average molecular weight of 500 or more. The ratio NCO / OH of the molar amount of the isocyanate group of the diisocyanate (b1) to the total molar amount of the hydroxyl groups of the polyol (b2) and the polyol (b3) is 3 or more and 30 or less.

15. The optical resin composition according to claim 14, wherein The mass ratio of the alicyclic polyisocyanate to the aliphatic diisocyanate is 0 / 100 or more and 30 / 70 or less.

16. The optical resin composition according to claim 14, wherein The mass ratio of the polyol (b3) to the polyol (b2) is (b3) / (b2) of 0.1 / 99.9 or more and 99.9 / 0.1 or less, and With respect to 100 parts by mass of the diisocyanate (b1), The content of the polyol (b2) is 0.1 parts by mass or more and 250 parts by mass or less, The content of the polyol (b3) is 0.1 parts by mass or more and 190 parts by mass or less.

17. The optical resin composition according to claim 14, wherein The mass ratio (b3) / (b2) of the polyol (b3) to the polyol (b2) is 5 / 95 or more and 80 / 20 or less, and With respect to 100 parts by mass of the diisocyanate (b1), The content of the polyol (b2) is 0.1 parts by mass or more and 210 parts by mass or less, The content of the polyol (b3) is 1 part by mass or more and 140 parts by mass or less.

18. The optical resin composition according to claim 14, wherein The mass ratio (b3) / (b2) of the polyol (b3) to the polyol (b2) is 5 / 95 or more and 80 / 20 or less, and With respect to 100 parts by mass of the diisocyanate (b1), The content of the polyol (b2) is 1.7 parts by mass or more and 42 parts by mass or less, The content of the polyol (b3) is 10 parts by mass or more and 60 parts by mass or less.

19. The optical resin composition according to claim 14, wherein The polyol (b2) and the polyol (b3) are at least one polyol selected from the group consisting of polyester polyols, polyether polyols, epoxy polyols, polyolefin polyols, and polycarbonate polyols.

20. The optical resin composition according to claim 1 or 2, wherein The isocyanate group content of the cross-linking agent component (B) is 1% by mass or more and 10% by mass or less.

21. The optical resin composition according to claim 1 or 2, wherein The isocyanate group content of the cross-linking agent component (B) is 2.7% by mass or more and 8.2% by mass or less.

22. The optical resin composition according to claim 1 or 2, wherein The acrylic polymer (A) further contains 0.01 parts by mass or more and 0.5 parts by mass or less of a silane coupling agent (C) based on 100 parts by mass of the acrylic polymer (A).

23. The optical resin composition according to claim 1 or 2, wherein The crosslinking agent component (B) contains one or more selected from the group consisting of isocyanate compounds other than the aliphatic or alicyclic polyisocyanates, carbodiimide compounds, oxazoline compounds, polyfunctional acrylate monomers, peroxides, titanium coupling agents, zirconium compounds, metal aluminum chelates, hydrazide compounds, epoxy crosslinking agents, thermal acid generators and photoacid generators.

24. The optical resin composition according to claim 1 or 2, wherein The crosslinking agent component (B) was applied on glass and stored at 23° C. and 65% humidity for 168 hours to form a cured film with a thickness of 40 μm having a pendulum hardness of 60 times or less at 23° C. 25 . An optical resin sheet obtained by curing the optical resin composition according to claim 1 by heat or light.

26. The optical resin sheet according to claim 25, wherein The optical resin sheet has a thickness of 1 μm or more and 1000 μm or less.

27. The optical resin sheet according to claim 25 or 26, wherein The following optical resin sheet is bonded to a SUS304BA plate as an adherend, and after being reciprocally pressed once using a 2kg roller and aging at 23°C for 30 minutes, the 180-degree peel adhesion measured at 23°C and a speed of 300 mm / min is 2.0 N / 20 mm or more and 65 N / 20 mm or less. The optical resin sheet is an optical resin sheet having a thickness of 70 μm, a width of 20 mm and a length of 100 mm, obtained by coating the optical resin composition on a polyethylene terephthalate film having a thickness of 25 μm, drying at 125°C for 3 minutes to cure, and then storing at 23°C and 50% RH for 7 days, and having a single side with the polyethylene terephthalate film having a thickness of 70 μm, a width of 20 mm and a length of 100 mm.

28. The optical resin sheet according to claim 25 or 26, wherein The following optical resin sheet is pasted on a SUS304BA plate as an adherend in an overlapping manner within a range of 25 mm in width and 25 mm in length, and is reciprocally pressed once using a 2 kg roller and aged at 23° C. for 1 hour. After further ripening at 40° C. for 30 minutes, a 500 g weight is hung at the lower end of the optical resin sheet at 40° C. for 1 hour, and then the offset of the optical resin sheet when it is restored to 23° C. is less than 2 mm / hour. The optical resin sheet is: an optical resin composition is applied to a polyethylene terephthalate film with a thickness of 25 μm, dried at 125° C. for 3 minutes to cure, and then stored at 23° C., 50% RH for 7 days, and the optical resin sheet has a thickness of 70 μm, a width of 25 mm, and a length of 130 mm on one side of the polyethylene terephthalate film.

29. The optical resin sheet according to claim 25 or 26, wherein The following optical resin sheet is pasted on glass with a haze value of 0.1%, and the haze value measured by a haze meter is less than 2.0%. The optical resin sheet is: the optical resin composition is applied on a polyethylene terephthalate film with a thickness of 38 μm, dried at 125° C. for 3 minutes to cure, and then stored at 23° C. and 50% RH for 7 days, and the optical resin sheet with a thickness of 70 μm is obtained by peeling it from the polyethylene terephthalate film with a thickness of 70 μm.

30. The optical resin sheet according to claim 25 or 26, wherein The following optical resin sheet is stored at 23°C and 50% RH for 7 days, then wrapped in a mesh sheet, immersed in ethyl acetate at 23°C for 1 week, taken out and dried at 120°C for 2 hours, and the gel fraction calculated thereby is 40.0% by mass or more and 99.9% by mass or less, wherein the optical resin sheet is: the optical resin composition is applied on a release-treated polyethylene terephthalate film having a thickness of 38 μm, dried at 125°C for 3 minutes to cure, and then stored at 23°C and 50% RH for 7 days, and a 70 μm thick optical resin sheet is obtained by peeling off the release-treated polyethylene terephthalate film.

31. The optical resin sheet according to claim 25 or 26, wherein The following optical resin sheets were stacked in a thickness of 210 μm, cut into pieces with a width of 10 mm and a length of 40 mm, and then mounted in a tensile testing machine with a distance between chucks of 10 mm. The Young's modulus in the tensile test performed at a speed of 300 mm / min at 23° C. was 0.40 N / mm 2 The optical resin sheet is as follows: the optical resin composition is coated on a polyethylene terephthalate film having a thickness of 38 μm and subjected to a peeling treatment, and then dried at 125° C. for 3 minutes to cure, and then stored at 23° C. and 50% RH for 7 days to obtain an optical resin sheet having a thickness of 70 μm obtained by peeling off the polyethylene terephthalate film having a thickness of 70 μm.

32. The optical resin sheet according to claim 31, wherein The Young's modulus is 0.01 N / mm 2 above.

Citation Information

Patent Citations

  • Acrylic polyol and composition for two-pack urethane resin coating containing it

    JP1989261409A

  • Weatherable paint composition

    JP1991006273A

  • Adhesive composition, adhesive member, optical member, and electronic member

    JP2017132872A

  • Resin composition, resin layer, and laminated sheet

    CN109312139A

  • Novel polyisocyanate and process for producing the same

    CN1293682A